2011
DOI: 10.1007/s11664-011-1798-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of AlN Nucleation Temperature on the Growth of AlN Films via Metalorganic Chemical Vapor Deposition

Abstract: AlN epilayers were grown directly on sapphire (0001) substrates using a combined growth scheme, consisting of a low-temperature nucleation layer and a second layer grown by high-temperature pulsed atomic layer epitaxy via metalorganic chemical vapor deposition. With an emphasis on the nucleation layer, its growth temperature was varied from 470°C to 870°C, and obvious differences in the surface morphology, crystal quality, and strain states of the overall AlN epilayers were observed. Based on atomic force micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…In order to study further the influence on the crystal Ref. [19] studied the size of AlN island under different growth temperature modes, as can be seen from Fig. 6, the size of AlN islands grown under low-temperature mode is smaller than the size of those grown under intermediate temperature and high temperature [19], which coincides with AFM images results.…”
Section: Raman Scatteringsupporting
confidence: 76%
“…In order to study further the influence on the crystal Ref. [19] studied the size of AlN island under different growth temperature modes, as can be seen from Fig. 6, the size of AlN islands grown under low-temperature mode is smaller than the size of those grown under intermediate temperature and high temperature [19], which coincides with AFM images results.…”
Section: Raman Scatteringsupporting
confidence: 76%
“…AlN with Al polarity has been found to exhibit a smoother surface while AlN with mixed polarity (Al and N) has a rougher surface morphology [11][12][13]. On the other hand, precursors flow prior to the deposition of the NLs [9], thickness of the NLs, the density and the size of the nucleation islands (NIs) have been found to influence the quality of the AlN layers [14][15][16][17]. Nevertheless, studies on the initial stages of AlN growth are still scarce, when compared to GaN.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the Al adatoms on bare sapphire have higher mobility as the growth temperature increases; then, they could move to the sites with lower nucleation formation energy and tend to be a large nuclei size. 36,37 According to our early work, the migration barrier (0.07 eV) of the Al atom on graphene is lower than that of sapphire (0.21 eV), 31 and AlN prefers to nucleate at the wrinkles and broken boundaries of graphene, in which the N atoms doping easily happens, then, providing a lower Al absorption energy. 38 For the lowest temperature of 950 °C, the insufficient mobility of Al adatoms results in higher normal growth rate than that of the lateral; thus, numerous AlN nuclei generate.…”
Section: ■ Results and Discussionmentioning
confidence: 91%